Assessment of Factors Affecting Attendance of Antenatal Care in Kagote Health Center III, Kabarole District, Uganda - Apiso, Margaret (Student’s Journal of Health Research Africa, 2021)
Background: Antenatal care is generally thought to be an effective method of improving outcomes in pregnant women and their babies, although many specific Antenatal Care practices have not been subject to rigorous evaluation Methodology: A descriptive cross-sectional study was carried out in Kagote HCIII aimed at assessing the factors affecting ANC attendance in the Kabarole district. Using a convenience sampling method, Kagote HCIII was chosen by the random sampling method. A sample of 100 respondents was interviewed. Questionnaires were used to obtain data from the individuals and these were in form of closed and open-ended questions. Results: The majority of the respondents 92(92%) used ANC information in subsequent pregnancies. 48(48%) said that multiparous women did not need to attend ANC if they were healthy while 12% were not sure. Challenges include long distance from the ANC clinic 32(13%), harsh health service providers 8(3%), lack enough support from husbands 22(9%), segregation and discrimination 12(5%), negative attitude towards ANC 16(7%), high transport costs 37(15.4%), lack of enough money 43(18%), lack of enough time 10(4%), too much workload at home 16(7%), long waiting time 20(8.3%), unavailability of some drugs at times 24(10%). Conclusion and recommendation: The factors affecting ANC attendance in Kagote HCIII are; age, occupation, education level, marital status, address, the number of health workers, their cadre, skill, authority, knowledge, nature, the services they and how they offer them, availability of incentives like drugs, multiparity, the order of pregnancy and the challenges mentioned above. There is a need for the MOH to continue sensitizing people about the importance of ANC attendance, outreaches by the health facility to the community to offer the service and encourage attendance, a collaboration between the health facility and the village health team continued health education of women of reproductive age about ANC and its attendance.